2009
DOI: 10.1002/jcu.20593
|View full text |Cite
|
Sign up to set email alerts
|

Parotid gland involvement in sarcoidosis: Sonographic features

Abstract: Because of the lack of specificity of US findings in sarcoidosis involvement of the parotid gland, sarcoidosis should be considered in the differential diagnosis of parotid gland lesions in the proper clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
1
8
0
2
Order By: Relevance
“…We found a Hočevar score above the control range in approximately 19% of our sample, and in 37% when using a cutoff score of 15, as suggested in some studies . A case series described US findings of the parotid gland of 6 patients with histologically proven sarcoidosis of the parotid gland with sonographic features ranging from nodal enlargement to diffuse or partial involvement of the parotid gland, with various degrees of echogenicity and vascularity . However, we did not detect any differences in lymph nodes or vascularity among our cohorts, and we could not distinguish the glandular appearance of the sarcoidosis subjects with abnormal salivary glands from those with Sjögren's syndrome.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…We found a Hočevar score above the control range in approximately 19% of our sample, and in 37% when using a cutoff score of 15, as suggested in some studies . A case series described US findings of the parotid gland of 6 patients with histologically proven sarcoidosis of the parotid gland with sonographic features ranging from nodal enlargement to diffuse or partial involvement of the parotid gland, with various degrees of echogenicity and vascularity . However, we did not detect any differences in lymph nodes or vascularity among our cohorts, and we could not distinguish the glandular appearance of the sarcoidosis subjects with abnormal salivary glands from those with Sjögren's syndrome.…”
Section: Discussionsupporting
confidence: 52%
“…Another investigator, blinded to the underlying diagnosis and clinical evaluation, analyzed the US video clip images for salivary gland US score (SGUS) using the Hočevar protocol (parenchymal echogenicity, homogeneity, hypoechoic areas, hyperechoic foci, and border visibility) , Doppler signal, hyperechoic septae, and lymph node characteristics. Intraglandular lymph nodes were evaluated for number, shape, size, group configuration, and pattern of Doppler flow .…”
Section: Methodsmentioning
confidence: 99%
“…MALT lymphoma should be excluded by open biopsy when enlarged intraparotideal lymph nodes are diagnosed in SS (Fig. 3) [19]. It has been estimated that MALT lymphoma originates in 510% of primary SS [1].…”
Section: Discussionmentioning
confidence: 99%
“…However, Teymoortash, et al [9].found that ultrasound findings had poor diagnostic specificity for sarcoidosis. While there are pathognomonic findings on certain imaging and histologic studies, a reliable modality for parotid assessment is yet to be determined.…”
Section: Diagnosismentioning
confidence: 97%